If \[\sin \theta =3\sin \left( \theta +2\alpha \right),\] then the value of \[\tan \left( \theta +\alpha \right)+2\tan \alpha \] is:
A. 3
B. 2
C. 1
D. 0
Answer
Verified
509.1k+ views
Hint: Use the Componendo Dividendo rule in the given expression. Apply trigonometric identities and simplify the expression to get the expression as \[\tan \left( \theta +\alpha \right)+2\tan \alpha \].
Complete step by step solution:
Given is the expression \[\sin \theta =3\sin \left( \theta +2\alpha \right)\]
\[\therefore \dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=3.\]
Let us use the Componendo Dividendo rule to solve the above expression.
Componendo Dividendo is a theorem on proportions which is used to perform calculations and reduce the number of steps.
According to Componendo Dividendo if \[\dfrac{a}{b}=\dfrac{c}{d},\]then it implies that \[\dfrac{a+b}{a-b}=\dfrac{c+d}{c-d}.......(1)\]
Thus applying Componendo Dividendo rule in the expression in equation (1),
\[\dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=\dfrac{3}{1}......(2)\]
Where,
\[\begin{align}
& a=\sin \theta \\
& b=\sin \left( \theta +2\alpha \right) \\
& c=3 \\
& d=1 \\
\end{align}\]
\[\begin{align}
& \therefore \dfrac{a+b}{a-b}=\dfrac{c+d}{c-d} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{3+1}{3-1} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{4}{2}=2......(3) \\
\end{align}\]
We know the trigonometric identities,
\[\begin{align}
& \operatorname{sinx}+siny=2sin\left( \dfrac{x+y}{2} \right)\cos \left( \dfrac{x-y}{2} \right) \\
& \sin x-\sin y=2\cos \left( \dfrac{x+y}{2} \right)\sin \left( \dfrac{x-y}{2} \right) \\
\end{align}\]
Let us apply these identities in equation (3).
\[x=\theta \]and\[y=\left( \theta +2\alpha \right)\].
\[\therefore \dfrac{2\sin \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\cos \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}{2\cos \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\sin \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}=2\]
By simplifying the expression, we get,
\[\begin{align}
& \Rightarrow \dfrac{\sin \left( \dfrac{2\theta +2\alpha }{2} \right)\cos \left( \dfrac{-2\alpha }{2} \right)}{\cos \left( \dfrac{2\theta +2\alpha }{2} \right)\sin \left( \dfrac{-2\alpha }{2} \right)}=2 \\
& \Rightarrow \dfrac{\sin \left( \theta +\alpha \right)\cos \left( -\alpha \right)}{\cos \left( \theta +\alpha \right)\sin \left( -\alpha \right)}=2 \\
\end{align}\]
The cosine is an even function, thus \[\cos (-\alpha )=\cos \alpha\].
The sine is an odd function, so \[sin(-\alpha )=-\sin \alpha \].
\[\dfrac{\sin \left( \theta +\alpha \right)\cos \left( \alpha \right)}{-\cos \left( \theta +\alpha \right)\sin \left( \alpha \right)}=2\]. By cross multiplying, we get,
\[\Rightarrow \dfrac{\sin \left( \theta +\alpha \right)}{\cos \left( \theta +\alpha \right)}=\dfrac{-2\sin \alpha }{\cos \alpha }\].
We know that \[\tan \theta =\dfrac{\sin \theta }{\cos \theta }.\]
\[\begin{align}
& \therefore \tan (\theta +\alpha )=-2\tan \alpha \\
& \Rightarrow \tan (\theta +\alpha )+2\tan \alpha =0 \\
\end{align}\]
Thus we got the value of \[\tan (\theta +\alpha )+2\tan \alpha \] as 0.
Hence option D is the correct answer.
Note:
Remember the basic trigonometric identities like \[(sinA+sinB)\] and \[(sinA-sinB)\] which we have used here. They are very important for solving expressions like these. Just apply the formula and simplify it and you will get the answer.
Complete step by step solution:
Given is the expression \[\sin \theta =3\sin \left( \theta +2\alpha \right)\]
\[\therefore \dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=3.\]
Let us use the Componendo Dividendo rule to solve the above expression.
Componendo Dividendo is a theorem on proportions which is used to perform calculations and reduce the number of steps.
According to Componendo Dividendo if \[\dfrac{a}{b}=\dfrac{c}{d},\]then it implies that \[\dfrac{a+b}{a-b}=\dfrac{c+d}{c-d}.......(1)\]
Thus applying Componendo Dividendo rule in the expression in equation (1),
\[\dfrac{\sin \theta }{\sin \left( \theta +2\alpha \right)}=\dfrac{3}{1}......(2)\]
Where,
\[\begin{align}
& a=\sin \theta \\
& b=\sin \left( \theta +2\alpha \right) \\
& c=3 \\
& d=1 \\
\end{align}\]
\[\begin{align}
& \therefore \dfrac{a+b}{a-b}=\dfrac{c+d}{c-d} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{3+1}{3-1} \\
& \Rightarrow \dfrac{\sin \theta +\sin \left( \theta +2\alpha \right)}{\sin \theta -\sin \left( \theta +2\alpha \right)}=\dfrac{4}{2}=2......(3) \\
\end{align}\]
We know the trigonometric identities,
\[\begin{align}
& \operatorname{sinx}+siny=2sin\left( \dfrac{x+y}{2} \right)\cos \left( \dfrac{x-y}{2} \right) \\
& \sin x-\sin y=2\cos \left( \dfrac{x+y}{2} \right)\sin \left( \dfrac{x-y}{2} \right) \\
\end{align}\]
Let us apply these identities in equation (3).
\[x=\theta \]and\[y=\left( \theta +2\alpha \right)\].
\[\therefore \dfrac{2\sin \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\cos \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}{2\cos \left( \dfrac{\theta +\theta +2\alpha }{2} \right)\sin \left( \dfrac{\theta -\theta -2\alpha }{2} \right)}=2\]
By simplifying the expression, we get,
\[\begin{align}
& \Rightarrow \dfrac{\sin \left( \dfrac{2\theta +2\alpha }{2} \right)\cos \left( \dfrac{-2\alpha }{2} \right)}{\cos \left( \dfrac{2\theta +2\alpha }{2} \right)\sin \left( \dfrac{-2\alpha }{2} \right)}=2 \\
& \Rightarrow \dfrac{\sin \left( \theta +\alpha \right)\cos \left( -\alpha \right)}{\cos \left( \theta +\alpha \right)\sin \left( -\alpha \right)}=2 \\
\end{align}\]
The cosine is an even function, thus \[\cos (-\alpha )=\cos \alpha\].
The sine is an odd function, so \[sin(-\alpha )=-\sin \alpha \].
\[\dfrac{\sin \left( \theta +\alpha \right)\cos \left( \alpha \right)}{-\cos \left( \theta +\alpha \right)\sin \left( \alpha \right)}=2\]. By cross multiplying, we get,
\[\Rightarrow \dfrac{\sin \left( \theta +\alpha \right)}{\cos \left( \theta +\alpha \right)}=\dfrac{-2\sin \alpha }{\cos \alpha }\].
We know that \[\tan \theta =\dfrac{\sin \theta }{\cos \theta }.\]
\[\begin{align}
& \therefore \tan (\theta +\alpha )=-2\tan \alpha \\
& \Rightarrow \tan (\theta +\alpha )+2\tan \alpha =0 \\
\end{align}\]
Thus we got the value of \[\tan (\theta +\alpha )+2\tan \alpha \] as 0.
Hence option D is the correct answer.
Note:
Remember the basic trigonometric identities like \[(sinA+sinB)\] and \[(sinA-sinB)\] which we have used here. They are very important for solving expressions like these. Just apply the formula and simplify it and you will get the answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE